Racial disparities in BRCA testing and cancer risk management across a population‐based sample of young breast cancer survivors. Issue 13 (9th February 2017) - Cragun, Deborah; Weidner, Anne; Lewis, Courtney; Bonner, Devon; Kim, Jongphil; Vadaparampil, Susan T.; Pal, Tuya
Abstract : BACKGROUND: Breast cancer (BC) disparities may widen with genomic advances. The authors compared non‐Hispanic white (NHW), black, and Hispanic BC survivors for 1) cancer risk‐management practices among BRCA carriers and 2) provider discussion and receipt of genetic testing. METHODS: A population‐based sample of NHW, black, and Hispanic women who had been diagnosed with invasive BC at age 50 years or younger from 2009 to 2012 were recruited through the state cancer registry. Multiple logistic regression was used to compare cancer risk‐management practices in BRCA carriers and associations of demographic and clinical variables with provider discussion and receipt of testing. RESULTS: Of 1622 participants, 159 of 440 (36.1%) black women, 579 of 897 (64.5%) NHW women, 58 of 117 (49.6%) Spanish‐speaking Hispanic women, and 116 of 168 (69%) English‐speaking Hispanic women underwent BRCA testing, of whom 90 had a pathogenic BRCA mutation identified. Among BRCA carriers, the rates of risk‐reducing mastectomy and risk‐reducing salpingo‐oophorectomy were significantly lower among black women compared with Hispanic and NHW women after controlling for clinical and demographic variables ( P = .025 and P = .008, respectively). Compared with NHW women, discussion of genetic testing with a provider was 16 times less likely among black women ( P < .0001) and nearly 2 times less likely among Spanish‐speaking Hispanic women ( P = .04) after controlling for clinical and sociodemographic factors. CONCLUSIONS: The current results suggest that the rates of risk‐reducing salpingo‐oophorectomy are lower among black BRCA carriers compared with their Hispanic and NHW counterparts, which is concerning because benefits from genetic testing arise from cancer risk‐management practice options. Furthermore, lower BRCA testing rates among blacks may partially be because of a lower likelihood of provider discussion. Future studies are needed to improve cancer risk identification and management practices across all populations to prevent the widening of disparities. Cancer 2017;123:2497–05. © 2017 American Cancer Society . Abstract : Among BRCA carriers, the lower rates of risk‐reducing salpingo‐oophorectomy among blacks compared with Hispanics and non‐Hispanic whites is concerning and may reduce benefits from genetic testing. Furthermore, lower rates of BRCA testing among blacks may be attributed in part to lower likelihood of provider discussion, suggesting the need to develop and implement multilevel interventions.